Changes in Soil Chemistry After 17 Years in Urban and Rural Forest Patches - Yesilonis, Ian; Giorgio, Vincent; Hu, Yinhong; Pouyat, Richard; Szlavecz, Katalin (Frontiers in Ecology and Evolution, 2022)
Cycling of carbon (C), nitrogen (N), calcium (Ca), phosphorus (P), and sulfur (S) is an important ecosystem service that forest soils provide. Humans influence these biogeochemical processes through the deposition of atmospheric pollutants and site disturbances. One way to study these potential anthropogenic trajectories is through long-term monitoring in association with human-caused environmental gradients such as urban-rural gradients. The objective of this study was to characterize changes in surface soil chemistry of urban, suburban and rural forest patches in the Baltimore Metropolitan area. Soil composite samples (0-10 cm) were analyzed for macro- and micronutrients, pH, and C. A total of 12 sites in forest patches dominated by white oak (Quercus alba) and tulip poplar (Liriodendron tulipifera) were established in 2001, and resampled in 2018. We hypothesized that after almost two decades 1) concentrations of N, Ca, and P, as well as soil pH would be higher, especially in urban forest patches due to local deposition; 2) S levels would be lower due to decreased regional atmospheric deposition and; 3) total soil C would increase overall, but the rate of increase would be higher in the urban end of the gradient due to increased NPP. Overall, means of Ca concentration, pH, and C:N ratios significantly changed from 2001 to 2018. Calcium increased by 35% from 622 to 844 mg kg-1, pH increased from 4.1 to 4.5, and C:N ratios decreased from 17.8 to 16.7. Along the gradient, Ca, N, P, and S were statistically significant with Ca concentration higher in the urban sites; S and N higher in the suburban sites; and P lower in the urban sites. Confounding factors, such as different geologic parent material may have affected these results. However, despite the unique site conditions, patterns of surface soil chemistry in space and time implies that local and regional factors jointly affect soil development in these forest patches. The increase in pH and Ca is especially notable because other long-term studies demonstrated changes in the opposite direction.